KNOWLEDGE, ATTITUDE AND PRACTICE OF INFECTION CONTROL AMONG DENTAL PRACTITIONERS IN ISLAMIC INTERNATIONAL DENTAL HOSPITAL,RIPHAH - Ufaq Rao; Abdul Razaq Khan; Zarnab Rizwan; Ghina Rizwan; Syed Hamza Zia (Journal of Rawalpindi Medical College)
Objective: The aim of the study was to investigate the knowledge, attitude and practices among  dental practitioners at a dental hospital in Islamabad.